AB0931 Persistence with subcutaneously administered biologics among patients with psoriatic arthritis: analyses from a us claims database. (12th June 2018) - Oelke, K.; Chambenoit, O.; Majjhoo, A.; Gray, S.; Higgins, K.; Hur, P.
Abstract : Background: Persistence with biologic therapies among patients with psoriatic arthritis (PsA) provides insight into the real-world effectiveness of biologics in routine clinical practice. With different dosing schedules and durations of action of currently available biologics, measuring persistence using varying treatment gap cutoffs may better guide physicians in their treatment decisions. Objectives: To evaluate the persistence of subcutaneously (SC) administered biologics in patients with PsA. Methods: Patients with ≥1 pharmacy claim for an FDA–approved SC biologic (adalimumab, certolizumab pegol, etanercept, golimumab, and secukinumab) for the treatment of PsA between 01/15/2016 and 07/31/2017 were identified in the Truven Health Analytics MarketScan Commercial and Medicare Supplemental Databases. Eligible patients were aged ≥18 years at the time of biologic initiation (index date) and continuously enrolled with medical and pharmacy claims ≥12 months prior to (baseline period) and ≥12 months after the index date. Patients had ≥1 PsA diagnosis (ICD-9-CM 696.0 or ICD-10-CM L40.5x) and no pharmacy claims for the index biologic during the baseline period. Persistence over 12 months was measured as the discontinuation rate and number of days persistent on the biologic therapy from the index date to reported treatment gaps of ≥45, ≥90, and ≥180 days based on clinical expert opinion, or the end of follow-up if no gap was observed. The median time to discontinuation of the index biologic over 12 months was assessed by Kaplan-Meier analysis for each treatment gap cutoff. Results: A total of 1558 patients with PsA enrolled in the analysis initiated SC biologics, including adalimumab (n=720), certolizumab pegol (n=93), etanercept (n=426), golimumab (n=64), and secukinumab (n=255). Overall, 680 patients (43.6%) discontinued their index biologic therapy during 12 month follow-up. The 12 month discontinuation rate for each treatment gap cutoff was lowest with secukinumab compared with other SC biologics (51.8%, 36.5%, and 21.6% for patients with treatment gaps≥45 days, ≥90 days, and ≥180 days, respectively). Mean days persistent on the index biologic was the highest with secukinumab for each treatment gap cutoff (254.5 days, 282.8 days, and 307.5 days for patients with treatment gaps≥45 days, ≥90 days, and ≥180 days, respectively) and the lowest with certolizumab pegol (218.1 days and 240.7 days for patients with treatment gaps≥45 days and ≥90 days, respectively) and etanercept (270.7 days for patients with a treatment gap ≥180 days; table 1 ). The median (95% CI) time to discontinuation for patients with a treatment gap ≥45 days was the highest with secukinumab (308 [238 to >365] days) and lowest with certolizumab pegol (216 [155 to 274] days). Median time to discontinuation could not be calculated for patients with treatment gaps≥90 days or ≥180 days due to low event rates and limited follow-up. Conclusions: Patients who initiated secukinumab showed higher persistence over 12 months of follow-up compared with the other SC biologics assessed, regardless of the treatment gap. Acknowledgements: This study was sponsored by Novartis Pharmaceuticals Corporation, East Hanover, NJ. Disclosure of Interest: K. Oelke Consultant for: Novartis Pharmaceuticals Corporation, Speakers bureau: AbbVie, Amgen, Bristol-Meyers Squibb and Pfizer, O. Chambenoit Employee of: Novartis Pharmaceuticals Corporation, A. Majjhoo Grant/research support from: Novartis Pharmaceuticals Corporation, Consultant for: Novartis Pharmaceuticals Corporation, Speakers bureau: Novartis Pharmaceuticals Corporation, S. Grey Employee of: Truven Health Analytics, an IBM Company, K. Higgins Employee of: Truven Health Analytics, an IBM Company, P. Hur Employee of: Novartis Pharmaceuticals Corporation